Flaw Imaging Technique for Plate-Like Structures Using Scanning Laser Source Actuation - Changgil Lee; Seunghee Park (Shock and Vibration)
Recently, the longitudinal, shear, and surface waves have been very widely used as ultrasonic wave-based exploration methods to identify internal defects of host structures. In this context, a noncontact nondestructive testing (NDT) method is proposed to detect the damage of plate-like structures and to identify the location of the damage. To achieve this goal, a scanning laser source actuation technique is utilized to generate a guided wave and scans a specific area to find damage location more precisely. The ND:YAG pulsed laser is used to generate Lamb wave and a piezoelectric sensor is installed to measure the structural responses. The measured responses are analyzed using 3-dimensional Fourier transformation (3D FT). The damage-sensitive features are extracted by wavenumber filtering based on the 3D FT. Then, flaw imaging techniques of a plate-like structure are conducted using the damage-sensitive features. Finally, the plates with notches are investigated to verify the effectiveness and the robustness of the proposed NDT approach.